Estudo de parâmetros cinéticos do sistema comercial Bac-to-Bac® para produção de proteínas recombinantes - Corrêa, Thaís Portantiolo (2011)
The expression system of recombinant proteins in insect cells/baculovirus (BEVS) was described and introduced in 1983 and since then has become a powerful tool for the production of recombinant proteins of biotechnological interest. This work studied the kinetics of Bac-to-BacR Baculovirus Expression System (Invitrogen ) used for the production of recombinant proteins, evaluating growth patterns and consumption of nutrients from Sf-9 insect cells infected with this commercial bacmid and determining the effect of viral inoculum. For this, Sf-9 cells grew at 29oC in T flasks containing 5 mL of SF-900 II medium or Schott bottles with working volume of 15 mL and orbital shaking at 90 rpm. UFLAG-286 cells were also tested at 29°C in TC-100 medium supplemented with 10% bovine fetal serum. The baculovirus used were the Autographa californica nuclear polyhedrosis virus (AcMNPV) as a wild baculovirus infection model, the bacmid extracted from DH10Bac bacteria and transposed with the transfer vector empty (pFastBac 1), called Bac sprec and the bacmid recombinant AcNPV with the GUS coding sequence of the gene β- glucuronidase, used as a standard for transposition experiments and transfection. Cells were infected at different times (TOI), on the initial phase, the exponential phase or stationary phase of cell growth, and with different multiplicities of infection (MOI) (0.01, 0.1, 1 and 10). It was observed that the MOI does not influence the viral replication, because even with the low MOI the cell growth was completely inhibited. TOI had already affected the production of total cell proteins, and infection in the early exponential phase was that obtained the highest number of total proteins. The supplementation of the cultivation with Bac sprec with serine and glutamine did not lead to increased viral production. The supernatant of cultures infected with Bac sprec was able to inhibit cell death where there was induction of apoptosis by terbutyl, indicating contain some protein with anti-apoptotic activity. This effect was not observed on wild baculovirus.